FIBER FOOD CONTENT AND ANALOG RICE FAVOR LEVEL WITH TALAS FLOUR AND COCONUT FLOUR - Nova P Kumolontang; Mariati Edam (Balai Riset Dan Standardisasi Industri Manado, 2020)
Analog rice can be made from various types of flour containing carbohydrates, such as taro flour or a mixture of several types of flour. Carbohydrate content in taro flour is expected to be a food source of alternative carbohydrate food. Taro flour has high amylopectin which gives a high stickiness, for that it is necessary to add coconut flour which has fiber and amylose content so that it can produce analog rice which is preferred. The purpose of this study was to determine the effect of taro flour and coconut flour composition on food fiber content and panelist preference level of analog rice This research uses method with experimental design that is Completely Randomized Design (CRD) with the treatment of taro flour and coconut flour as many as six levels of treatment made in the form of formulations namely A (taro flour 90%: 10% coconut flour), B (flour 85% taro: 15% coconut flour), C (80% taro flour: 20% coconut flour), D (75% taro flour: 25% coconut flour), E (70% taro flour: 30% coconut flour). The results showed that the content of insoluble food fiber ranged from 4.95 to 7.39% while the soluble food fiber ranged from 2.13 to 2.72%. Organoleptic assessment of analog rice includes color (3.41-3.68), texture (3.23-3.59), appearance (3.30-3.59) while assessment of rice from analog rice is texture (3, 41-3.66), taste (3,50-3,91), color (3,25-3,42) and odor (3,50-3,83). Analog rice made from taro flour and coconut flour contains dietary fiber, which is soluble and insoluble fiber, which is beneficial to health as well as the panelists' preference level for the best analog rice, namely composition of taro flour 75%: 25% coconut flour.Keywords: analog rice, coconut flour, taro flour